UNITY 3D GAME DEVELOPMENT designed for passionate game developers, engineered to build professional games - DAVIS, ANTHONY (PACKT PUBLISHING LIMITED, 2022)
Create ready-to-play 3D games with reactive environments, sound, dynamic effects, and more! Key Features Build a solid foundation for game design and game development Understand the fundamentals of 3D such as coordinates, spaces, vectors, and cameras Get to grips with essential Unity concepts including characters, scenes, terrains, objects and more Book Description This book, written by a team of experts at Unity Technologies, follows an informal, demystifying approach to the world of game development. You'll learn the 3D and C# fundamentals before starting to build one short segment of the full game -- a vertical slice. With every progressing chapter, you'll learn to improve this game (alongside building your own) to make it ready to pitch to studios. Within Unity 3D Game Development, you will learn to: Design and build 3D characters, and the game environment Think about the users' interactions with your game Develop the interface and apply visual effects to add an emotional connection to your world Grasp a solid foundation of sound design, animations, and lightning to your creations Build, test, and add final touches The book is split between expert insights that you'll read before you look into the project on GitHub to understand all the underpinnings. This way, you get to see the end result, and you're allowed to be creative and give your own thoughts to design, as well as work through the process with the new tools we introduce. Join the book community on Discord: Read this book with Unity game developers, and the team of authors. Ask questions, build teams, chat with the authors, participate in events and much more. The link to join is included in the book. What you will learn Learn fundamentals of designing a 3D game and C# scripting Design your game character and work through their mechanics and movements Create an environment with Unity Terrain and ProBuilder Explore instantiation and rigid bodies through physics theory and code Implement sound, lighting effects, trail rendering, and other dynamic effects Create a short, fully functional segment of your game in a vertical slice Polish your game with performance tweaks JOIN the 'book-club' to read alongside other users, Unity experts, and ask the authors when stuck Who this book is for Our goal with this book is to enable every reader to build the right mindset to think about 3D games, and then show them all the steps we took to create ours. The main target audience for this book is those with some prior knowledge in game development, though regardless of your experience, we hope to create an enjoyable learning journey for you.